Central sleep related breathing disorders - diagnostic and therapeutic features - Becker, Heinrich F. (German Medical Science GMS Publishing House, 2006)
Three classes of central SRBD are distinguished: 1. Central sleep apnea (CSA), 2. Cheyne-Stokes Respiration as a subgroup of CSA and 3. central hypoventilation syndromes. Reduced or completely absent central respiratory drive without upper airway obstruction is the common feature of central SRBD. Hypoventilation syndromes most often occur secondary in patients with neuromuscular, pulmonary or sceletal diseases or in patients with massive obesity. In patients with hypoventilation during sleep nocturnal and exertional dyspnea and headaches are frequently reported symptoms. Excessive daytime sleepiness is the key symptom in patients with central sleep apnea syndrome. Cheyne-Stokes Respiration is frequent in heart failure patients but in many cases does not cause symptoms specific for the breathing disorder. If there are symptoms or if ambulatory recording of breathing during sleep suggests a sleep related breathing disorder, polysomnography is then performed to definitively rule out or confirm the diagnosis and to initiate treatment, if needed. The indication for treatment in asymptomatic patients with central sleep apnea and Cheyne-Stokes Respiration may be difficult, as there are very little data concerning the long-term benefit in these patients. Symptomatic patients and those with severe central sleep apnea should be treated. Oxygen and CPAP may be effective in 20-30% of patients each. If these treatment options are ineffective, non-invasive pressure support ventilaiton can be used. In patients suffering from hypoventilation syndromes the treatment of choice is non-invasive pressure support ventilaiton combined with supplemental oxygen, if required.